Green economy in the sports sector and the impacts of future climate change: An analysis of opportunities and challenges for economic sustainability - Ahmed, Mustafa Issa Ali Al (International Journal of Innovative Research and Scientific Studies, 2025)
The study aimed to investigate the contribution of green economy technologies to confronting climate change in the Saudi sports sector. The researcher relied on the descriptive approach for the purposes of the study and chose the descriptive survey method because it was appropriate for the study methodology to achieve the objectives. The course included representatives of the sports industry in the Kingdom of Saudi Arabia. The study sample consisted of 1,420 individuals who were selected based on different categories within the study community. Two questionnaires were applied as data collection tools, indicating a strong focus on technology applications and the implementation of green and environmentally friendly policies by some sports institutions in the Kingdom of Saudi Arabia. Findings: The results demonstrated a strong positive relationship between the use of green economy technology and confronting climate impacts in the sports sector. It is believed that such technologies constitute a powerful tool for predicting the sustainability of the sports ecosystem in the Kingdom of Saudi Arabia. The practical implications of this study emphasize that integrating renewable energy sources, eco-friendly materials, and smart systems into sports facilities not only minimizes environmental harm but also promotes economic diversification aligned with Vision 2030. Additionally, they improve resource efficiency, such as water and energy management, while fostering positive societal attitudes toward sustainable sports practices.